'TAM 114' Wheat, Excellent Bread‐Making Quality Hard Red Winter Wheat Cultivar Adapted to the Southern High Plains. Issue 3 (30th August 2018) - Rudd, Jackie C.; Devkota, Ravindra N.; Ibrahim, Amir M.; Baker, Jason A.; Baker, Shannon; Lazar, Mark D.; Sutton, Russell; Simoneaux, Bryan; Opena, Geraldine; Rooney, Lloyd W.; Awika, Joseph M.; Liu, Shuyu; et al.
Abstract : 'TAM 114' (Reg. No. CV‐1146, PI 686860), a hard red winter wheat ( Triticum aestivum L.) cultivar with the experimental designation of TX07A001505, was developed and released by Texas A&M AgriLife Research in 2014. TAM 114 is an F6 –derived line from the cross 'TAM 111'/TX98A0050 made at Bushland, TX, in 1999. TAM 114 is an awned, medium‐maturing, semidwarf wheat with red glumes. It was released primarily for its extra‐strong baking properties as indicated by longer bake mix time, excellent mixing tolerance, and good loaf volume. TAM 114 has significantly higher grain yield than that of TAM 111 and 'TAM 112' in the Texas High Plains under both irrigated and dryland environments. It is high in grain volume weight, is resistant to leaf, stripe, and stem rusts, has a moderate level of resistance to Hessian fly biotypes GP and vH9, and has good acid soil tolerance. Compared with TAM 111 and TAM 112, which are currently the two most widely grown cultivars in Texas, TAM 114 has higher grain yield, higher grain volume weight, better leaf and stripe rust resistance, and better bread baking properties. It will provide a good complement to other hard red winter wheat cultivars for wheat producers, millers, and bakers and ultimately for consumers of wheat products in the southern US Great Plains.